2017
DOI: 10.3319/tao.2013.08.01.01(gsc)
|View full text |Cite
|
Sign up to set email alerts
|

A study of relative permeability parameters on rock cores using a two-phase flow test

Abstract: To ensure sequestration safety, confirming the injectivity of the reservoir rock formation is of critical importance, requiring studies of the rock permeability to uncover the fluid migration scenarios within the porous reservoir rock. Two-phase (super-critical CO 2 -brine) flow behavior following the post CO 2 injection is believed to be a dominating factor; its flooding behavior within the porous rock media needs to be further clarified prior to confirming the feasibility of domestic CO 2 geo-sequestration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In CO 2 geological storage engineering, the reservoir roof serves as the main isolator medium, and its permeability and porosity directly affect the CO 2 storage efficiency and the time of safe storage. Thus, scholars have carried out extensive experimental and theoretical research on rock permeability and pore structure [27][28][29][30][31][32]. Fatt et al [33] studied the relationship between sandstone permeability and overburden pressure/confining pressure and found that permeability was negatively correlated with the two pressure forms, and the variation was notable in the low-pressure area.…”
Section: Introductionmentioning
confidence: 99%
“…In CO 2 geological storage engineering, the reservoir roof serves as the main isolator medium, and its permeability and porosity directly affect the CO 2 storage efficiency and the time of safe storage. Thus, scholars have carried out extensive experimental and theoretical research on rock permeability and pore structure [27][28][29][30][31][32]. Fatt et al [33] studied the relationship between sandstone permeability and overburden pressure/confining pressure and found that permeability was negatively correlated with the two pressure forms, and the variation was notable in the low-pressure area.…”
Section: Introductionmentioning
confidence: 99%